2006
DOI: 10.1038/sj.jid.5700586
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans Cells Release Prostaglandin D2 in Response to Nicotinic Acid

Abstract: Nicotinic acid, used for atherosclerosis treatment, has an adverse effect of skin flushing. The flushing mechanism, thought to be caused by the release of prostaglandin D(2) (PGD(2)), is not well understood. We aimed to identify which cells mediate the flushing effect. Nicotinic acid receptor (GPR109A) gene expression was assessed in various tissues and cell lines. Cells expressing GPR109A mRNA were further assayed for PGD(2) release in response to nicotinic acid. Of all samples, only skin was able to release … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
138
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(144 citation statements)
references
References 25 publications
5
138
0
1
Order By: Relevance
“…Recent work examining the mechanism of niacin-induced flushing has revealed that it is mediated by GPR109A (16) and requires the release of PGD 2 and activation of DP1 receptors in the skin (18) and, finally, that the PGD 2 release is mediated by epidermal Langerhans cells (17,19). Based on the results shown herein we would speculate that GPR109A agonists activate a MAP kinase-mediated release of PGD 2 from Langerhans cells, leading to the cutaneous vasodilation responsible for the flushing response.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…Recent work examining the mechanism of niacin-induced flushing has revealed that it is mediated by GPR109A (16) and requires the release of PGD 2 and activation of DP1 receptors in the skin (18) and, finally, that the PGD 2 release is mediated by epidermal Langerhans cells (17,19). Based on the results shown herein we would speculate that GPR109A agonists activate a MAP kinase-mediated release of PGD 2 from Langerhans cells, leading to the cutaneous vasodilation responsible for the flushing response.…”
Section: Resultsmentioning
confidence: 78%
“…Recent work has begun to elucidate the mechanism by which nicotinic acid induces flushing (16 -19). GPR109A has been shown to mediate nicotinic acid-induced flushing through release of prostaglandin D2 (PGD 2 ) and involves the activation of the DP1 receptor and possibly a PGE 2 receptor (EP2 or EP4) (16, 18) Recent work has further supported the hypothesis that it is GPR109A receptors on Langerhans cells in the skin that mediate nicotinic acid-induced flushing through generation of PGD 2 (17,19).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…Formation of AA is the rate-limiting step in the biosynthesis of the vasodilatory PGD 2 and E2 (PGE 2 ) (Murakami and Kudo 2004) These prostaglandins bind to specific prostanoid receptors on vascular smooth muscle within the skin. Activation of prostanoid receptors dilates cutaneous blood vessels (Lai et al, 2007), and a visible skin flush arises from the ensuing increased blood flow (BenyĂł et al, 2005;Maciejewski-Lenoir et al, 2006;Morrow et al, 1989Morrow et al, , 1992.…”
Section: Mechanism Of the Niacin Flush Responsementioning
confidence: 99%